Ghana : 2019 Article IV Consultation; Press Release; Staff Report; and Statement by the Executive Director for Ghana. (IMF Staff Country Reports; Country Report ;, 2019)
This 2019 Article IV Consultation with Ghana highlights discussions focused on strengthening institutions and policies to preserve macroeconomic stability and promote inclusive growth, building on the authorities' 'Ghana beyond Aid' strategy. The government headline deficit is projected to reach 4.7 percent of gross domestic product in 2019, driven by lower-than-expected revenues, spending on flagship programs, and unexpected security outlays due to emerging security challenges in the region. Medium-term prospects are favorable, with robust growth driven mostly by the extractive sector. Election-related spending pressures in 2020 constitute the main risk to the baseline scenario. Fiscal risks in the financial and energy sectors could also impact the government deficit. Government borrowing needs are exposed to rollover risk that should be carefully managed as financing conditions could tighten. The commitment to the new fiscal rules is expected to help maintain fiscal discipline, as reflected in the unchanged policy baseline. A more ambitious fiscal stance is called for to reduce macroeconomic risks, accelerate debt reduction, and strengthen the external balance.